Molecular detection of airborne Emergomyces africanus, a thermally dimorphic fungal pathogen, in Cape Town, South Africa - Schwartz, Ilan S. (PLoS Negl Trop Dis, 2018)
Emergomyces africanus is a thermally dimorphic fungus that causes a systemic mycosis in immunocompromised persons in South Africa. Infection is presumed to follow inhalation of airborne propagules. We developed a quantitative PCR protocol able to detect as few as 5 Es. africanus propagules per day. Samples were collected in Cape Town, South Africa over 50 weeks by a Burkard spore trap with an alternate orifice. We detected Es. africanus in air samples from 34 days (10%) distributed over 11 weeks. These results suggest environmental exposure to airborne Es. africanus propagules occurs more commonly in endemic areas than previously appreciated.